PENGETAHUAN REMAJA TENTANG HIV/AIDS - Kumalasary, Diyanah (MIDWIFERY JOURNAL, 2021)
Background : Human Immunodeficiency Virus (HIV) is a virus that causes decreased immunity and can cause a set of symptoms of a disease called Acquired immuno deficiency syndrom (AIDS). The phenomenon of people living with HIV/AIDS tends to increase in both developed and developing countries, including Indonesia. A total of 324 new cases were found throughout 2020 in Cirebon City.Objective : Adolescent knowledge about HIV/AIDS is expected to inhibit or prevent the spread of HIV/AIDS. Methods : The research design used is descriptive with cross sectional approach. Sampling with stratified random sampling technique. The number of samples was determined using the slovin formula, in order to obtain a sample of 142 adolescents who met the inclusion criteria. Result : The majority of adolescents who have sufficient knowledge are 92 people, the majority of respondents are 13-15 years old, 109 people are middle-school teenagers, 78 parents are included in the middle school education, 85 parents have high jobs, 82 respondents said they didn’t obtain information related to HIV/AIDS, based on information sources, the majority of adolescents get information related to HIV/AIDS from schools/lessons.Conclusion : From 142 respondents, the majority are in the age range of 13-15 yaers who are middle-aged adolescents and have sufficient knowledge related to HIV/AIDSSuggestion With a good level of knowledge related to HIV/AIDS, the hope is that it can prevent and reduce the incidence of HIV/AIDS among adolescents.  Keywords : Knowledge, adolescent characteristics, HIV/AIDS. ABSTRAK Latar belakang : Human Immunodeficiency Virus (HIV) merupakan virus yang menyebabkan penurunan kekebalan tubuh dan dapat menimbulkan sekumpulan gejala penyakit yang disebut Aquired imuno deficiency syndrom (AIDS). Fenomena orang dengan HIV/AIDS jumlahnya cenderung meningkat baik di Negara maju maupun Negara berkembang termasuk Indonesia. Sebanyak 324 kasus baru ditemukan sepanjang 2020 di Kota CirebonTujuan : Pengetahuan remaja tentang HIV/AIDS diharapkan dapat menghambat atau mencegah penyebarluasan HIV/AIDS.Metode : Desain penelitian yang digunakan adalah deskriftif dengan pendekatan cross sectional. Pengambilan sampel dengan teknik Stratified Random Sampling. Jumlah sampel ditetukan menggunakan rumus Slovin, sehingga diperoleh sampel sebanyak 142 remaja yang memenuhi kriteria inklusi.Hasil penelitian : Mayoritas remaja yang memiliki pengetahuan cukup sebanyak 92 orang, umur responden mayoritas 13-15 tahun sebanyak 109 orang yang merupakan remaja menengah, pendidikan orangtua yang termasuk menengah terdapat 78 orang, sebanyak 85 orangtua mempunyai pekerjaan yang tergolong tinggi, 82 responden menyatakan tidak mendapatkan informasi terkait HIV/AIDS, berdasarkan sumber informasi, mayoritas remaja mendapatkan informasi terkait HIV/AIDS dari sekolah/pelajaranKesimpulan : Dari 142 responden, mayoritas berada pada rentang umur 13-15 tahun yang merupakan kelompok remaja menengah dan dengan tingkat pengetahuan cukup terkait HIV/AIDSSaran Dengan adanya tingkat pengetahuan yang baik terkait HIV/AIDS harapannya adalah dapat mencegah dan menurunkan angka kejadian HIV/AIDS pada kalangan remaja.   Kata Kunci : Pengetahuan, karakteristik remaja, HIV/AIDS.